Extremely Flexible Transparent Conducting Electrodes for Organic Devices. Issue 1 (23rd July 2013) - Jung, Sunghoon; Lee, Sunghun; Song, Myungkwan; Kim, Do‐Geun; You, Dae Sung; Kim, Jong‐Kuk; Kim, Chang Su; Kim, Tae‐Min; Kim, Kwon‐Hyeon; Kim, Jang‐Joo; Kang, Jae‐Wook
<x xml:space="preserve">Abstract</x> Extremely flexible transparent conducting electrodes are developed using a combination of metal‐embedding architecture into plastic substrate and ultrathin transparent electrodes, which leads to highly transparent (optical transmittance ≈93% at a wavelength of 550 nm), highly conducting (sheet resistance ≈13 Ω □−1), and extremely flexible (bending radius ≈ 200 μm) electrodes. The electrodes are used to fabricate flexible organic solar cells and organic light‐emitting diodes that exhibit performance similar or superior to that of devices fabricated on glass substrates. Moreover, the flexible devices do not show degradation in their performance even after being folded with a radius of ≈200 μm.